Cost-effectiveness of Carbetocin versus Oxytocin for Prevention of Postpartum Hemorrhage Resulting from Uterine Atony in Women at high-risk for bleeding in Colombia - Yaneth Gil-Rojas; Pieralessandro Lasalvia; Fabián Hernández; Camilo Castañeda-Cardona; Diego Rosselli (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To assess the cost-effectiveness of carbetocin versus oxytocin for prevention of postpartum hemorrhage (PPH) due to uterine atony after vaginal delivery/ cesarean section in women with risk factors for bleeding. Methods A decision treewas developed for vaginal delivery andanother one for cesarean, in which a sequential analysis of the results was obtained with the use of carbetocin and oxytocin for prevention of PPH and related consequences. A third-party payer perspective was used; only directmedical costs were considered. Incremental costs and effectiveness in terms of quality-adjusted life years (QALYs) were evaluated for a one-year timehorizon. The costs were expressed in 2016 Colombian pesos (1 USD = 3,051 Col$). Results In the vaginal delivery model, the average cost of care for a patient receiving prophylaxis with uterotonic agents was Col$ 347,750 with carbetocin and Col$ 262,491 with oxytocin,while theQALYs were 0.9980 and 0.9979, respectively. The incremental costeffectiveness ratio is above the cost-effectiveness threshold adopted by Colombia. In the model developed for cesarean section, the average cost of a patient receiving prophylaxis with uterotonics was Col$ 461,750 with carbetocin, and Col$ 481,866 with oxytocin, and the QALYs were 0.9959 and 0.9926, respectively. Carbetocin has lower cost and is more effective, with a saving of Col$ 94,887 per avoided hemorrhagic event. Conclusion In case of elective cesarean delivery, carbetocin is a dominant alternative in the prevention of PPH compared with oxytocin; however, it presents higher costs than oxytocin, with similar effectiveness, in cases of vaginal delivery.